APLIKASI ZPT URINE SAPI TERHADAP KEBERHASILAN STEK SIRIH MERAH (Piper crocatum Ruiz) - F. Silvi Dwi Mentari; Nur Hidayat; Yuanita Yuanita; Faradilla; Riama Rita Manullang; La Mudi; Rusmini (JURNAL AGRIMENT, 2022)
This study aimed to calculate the speed of growth characterized by the emergence of shoots and percentage of successful growth of red betel cuttings cuttings given plant growth regulator cow urine. The study consisted of two treatments, namely: first treatment, red betel cuttings soaked in concentration 30% cow urine, and second treatment, red betel cuttings soaked in concentration 50% cow urine. The results showed that immersion with cow urine in the first treatment (red betel cuttings soaked using cow urine by concentration 30%) and second (soaking red betel cuttings with concentration 50%) gave the same results in the speed of growth that showed speed buds appear on 5th day, while the best percentage growth of red betel cuttings in the second treatment was 100% followed by the first treatment of 83%.